Numerical solution of fuzzy differential equation using improved Runge-Kutta method - Rabiei, Faranak; Ismail, Fudziah (Global Science and Technology Forum, 2014)
In this paper a fuzzy Improved Runge-Kutta method for solving first-order fuzzy differential equations is proposed. The scheme is two step in nature and is based on the Improved Runge-kutta method for solving ordinary differential equations. Here, the fourth order method with three stages is explained. In this method some new parameter be exploited to increase the accuracy in comparison with other same stage existing methods. The convergence of the method is proven, and several numerical examples are experienced to illustrate the effectiveness of the method.